Written Corrective Feedback Employed by Lecturer on Students’ Writing - Rulik Setiani; Sigit Suharjono (International Journal of Contemporary Studies in Education, 2025)
Purpose – The aim of the study is to identify the types of written corrective feedback and find out the types that are frequently employed by lecturer of students’ writing in her feedback or correction. State the background of the study is Written corrective feedback is not only provided to students are able to develop, motivate, revise but also to do their writing well. Methodology – The researcher employed a qualitative descriptive research method. The instrument used was document. 19 students' writing as documents were analysed. Findings – the study show that lecturer used four types of written corrected feedback among 6 types. There were 1 direct corrective feedback, 332 indirect corrective feedback, 88 focused corrective feedback, and 6 unfocused corrective feedback. The researchers discovered that the lecturer was more likely to use indirect corrective feedback in giving feedback of students’ writing. Novelty – The study may provide practical recommendations for improving writing instruction by showing the effectiveness or challenges of particular feedback types used by lecturers. Significance – The findings benefit to lecturers who teach writing skills, there are many types of written corrective feedback. Lecturers should vary their feedback when making error corrections in students' written productions. For example, not only can most lecturers employed direct and indirect corrective feedback, but lectures can also employed other types of written corrective feedback, such as metalinguistics or reformulation feedback.